INTERNATIONAL CRIMINAL COURT DALAM HUMANITARIAN ACTION - Annisa Rengganis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2017)
The presence of the International Criminal Court (ICC) through its Roma1998 Statutes in 2002 at least provide fresh air for the law enforcement agencies for the international community. I rate, the presence of the ICC is a missing link after the formation of the International Court of Justice (ICJ) which only has authority over the country as its subject matter. Unlike the ICJ, ICC formation is motivated by the demand for justice for the many crimes incredible cruel (heinous crime), such as genocide (genocide), crimes against humanity (crimes against humanity), war crimes (war crimes) that has caused human casualties very large. As a case study this paper is a crime against humanity in Darfur are handled by ICC judiciary. In the present paper will see that so far, the international legal instruments are able to optimally ensnare the perpetrators of crimes against humanity. Thus, it is necessary that international criminal justice agencies have the authority to break the impunity and independent institution.